Intra‐articular treatment with hyaluronic acid associated with gold nanoparticles in a mechanical osteoarthritis model in Wistar rats. Issue 12 (29th April 2021) - Filho, Mario Cesar Búrigo; dos Santos Haupenthal, Daniela Pacheco; Zaccaron, Rubya Pereira; de Bem Silveira, Gustavo; de Roch Casagrande, Laura; Lupselo, Fernando Silva; Alves, Naiara; de Sousa Mariano, Samara; do Bomfim, Fernando Russo Costa; de Andrade, Thiago Antônio Moretti; Machado‐de‐Ávila, Ricardo Andrez; Silveira, Paulo Cesar Lock
Abstract: This study aimed to evaluate the effects of intra‐articular treatment with hyaluronic acid (HA) associated with GNPs in a mechanical model of osteoarthritis induced by median meniscectomy (MM). Fifty Wistar rats (2 months weighing between 250 and 300 g) were used, divided into five groups of 10 animals each: Sham, osteoarthritis (OA), OA + HA, OA + gold nanoparticles (GNPs), and OA + HA + GNPs. Intra‐articular treatment was started 30 days after the model was induced, with a frequency of 2 weeks for 60 days. Fifteen days after the last application, the animals were euthanized with the removal of the joint tissue for biochemical and histological analysis. The model used was able to mimic osteoarthritis, characterized by the presence of high levels of proinflammatory cytokines, oxidative stress, and degeneration of joint surfaces (Grade III, according to SCORE OARSI). The isolated use of HA or GNPs provided beneficial results to the joint; however, only the group subjected to the association between HA and GNPs showed the attenuation of oxidative stress and reduced proinflammatory markers, with a simultaneous increase in levels of anti‐inflammatory cytokines and growth factors. Upon histological analysis, only the OA + HA + GNPs group achieved the restoration of the thickness of the joint cartilage with reduced damage and return to the intact joint surface. The results found demonstrated that the association of GNPs with HA was able to reverse the deleterious effects caused by the model by inhibiting the progressive degeneration of joint surfaces, representing a promising treatment for osteoarthritis.